The Effect of Financial Literacy and Financial Attitude on Financial Management with Personality as an Intervening Variable on BRI Micro Credit Customers, Khatib Sulaiman Branch, Padang City - Guslindawati Guslindawati; Elfiswandi Elfiswandi; Lusiana Lusiana (Jurnal Multidisiplin Sahombu, 2026)
This study aims to examine the influence of financial literacy and financial attitudes on financial management, with personality as an intervening variable among BRI microcredit customers at the Khatib Sulaiman Branch in Padang City. Data collection was conducted through a survey and questionnaire distribution, with a sample of 95 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant influence of financial literacy on personality. There was a significant influence of financial attitudes on personality. There was a significant influence of financial literacy on financial management. There was a significant influence of financial attitudes on financial management. There was a significant influence of personality on financial management. Personality mediated the influence of financial literacy on personality. Personality mediated the influence of financial attitudes on personality.